The notion of commitment in selected works of Maishe Maponya - Moorosi, Mabitle (Rhodes University, Faculty of Humanities, Department of Drama, 1998)
This study is a critical analysis of selected works of the playwright Maishe Maponya namely, The Hungry Earth, Jika and Gangsters. The main thrust of the analysis of the thesis is centred on questions around what 'Commitment' might mean in literature and drama. This concept has appeared in many names and guises. In theatre, it has assumed names like Theatre of Commitment, Theatre of the Dispossessed, Theatre ofthe Oppressed, Theatre of Resistance, as well as Theatre of Radicalization (Bentley 1968; Boal 1974; Mda 1985; Maponya 1992). These names came into existence as a result of a concerted effort to refrain from the use of the traditional conventional theatre, which does not appear to address itself to societal problems - the preoccupation of Theatre of Commitment. Chapter One is principally concerned with the concept of Commitment and its implications in art and literature, more specifically in theatre. Further, the following interacting elements in South African theatre are highlighted: censorship, banning, detention and other restrictions, as well as DET education and religious institutions. Finally, Maponya is introduced, with his political inclinations and his views on art, together with the issue of theatricality in his plays. Chapter two initiates the proposed critical analysis with a focus on The Hungry Earth. The focus is on Theatre of Commitment and the background events that inspired Maponya's response. Chapter three concerns itself with the critical analysis of Jika, "a play about the making of revolutionaries in South Africa ... and serves a political purpose - as a recording of pivotal moment in South African history ... " (Haysom, 1988: 1). An attempt is made to assess the extent to which the playwright has succeeded or failed to strike a chord harmonious with the pronouncements quoted. Chapter four ends the critical analysis with the treatment of Gangsters. Here an observation is made on the fusing of the three personas, namely Rasechaba, Biko and Maponya, into one symbolic whole representing the image of Jesus Christ on the cross - the Saviour who sacrificed His life for the salvation of sinners. Maponya is seen to have sacrificed his time and energy for the liberation of the downtrodden. The conclusion summarizes the study by placing the selected works in their suitable perspective in respect of the notion of Commitment in literature, with particular reference to theatre. Maponya is seen to have played a commendable role in the liberation of his peoples' minds by teaching them the business of organizing revolutions, as well as by championing the liberation struggle.
Keywords: Maponya, Maishe; Commitment (Psychology) in literature